Fabrication of highly porous carbon as sulfur hosts using waste green tea bag powder for lithium-sulfur batteries - Seo, Seung-Deok; Choi, Changhoon; Kim, Byung-Kook; Kim, Dong-Wan (ELSEVIER SCI LTD, 2017)
An activated carbon (AC) was synthesized via pyrolysis of waste green tea bag powder at 600 degrees C and subsequent activation of the carbonized powder by KOH at 800 degrees C. The AC powder exhibited an irregular particle size but a large specific surface area and pore volume of 2015 m(2) g(-1) and 0.727 cm(3) g(-1), respectively, which were significantly enhanced values compared with those of the original waste green tea bag powder. Furthermore, we tested the AC for use as a sulfur host for a lithium-sulfur battery cathode using cyclic voltammetry and galvanostatic charge/discharge cycling.
Keywords: ACTIVATED CARBON; AMORPHOUS-CARBON; AQUEOUS-SOLUTION; ENERGY-STORAGE; ION BATTERY; ADSORPTION; KOH; TEMPERATURE; GRAPHENE; CATHODES